RESERVATION POLICY IN INDIA: PROFICIENT OR STERILE - Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Reservation can be described as “an effort to advance equal opportunities in government and educational institutions. It is often instituted for ensuring that minor groups are involved in every program within a community”. Reservation in India has a legal backing. The legislature, State and Central civil services, and other government industry units were guaranteed reservations. Few experts have criticised the reservation policy. They argue that we have totally failed to bring the poor on a par with the remainder of society. On the contrary, reservation policy often appears to seek to compensate the mistake performed all these years to the unprivileged. . In the present system only the persons who have already got the benefit of reservation are getting it time and again. But, poor persons who are in dire need of support from the Government may not get it as they do not belong to any reserved category. Hence there is a need to review the policy according to needs of the society.